Osmoregulation of juvenile marine goliath grouper (Epinephelus itajara) in low-salinity water - Lury N García; Clara L Sierra; Jeiver Perez; Frank Esquivel; Frank A Chapman (Revista Colombiana de Ciencias Pecuarias, 2013)
Background: goliath grouper (Epinephelus itajara) is an economically valuable marine species and an excellent candidate for domestication for aquaculture purposes. If this grouper can osmoregulate in lowsalinity water, its cultivation can provide socio-economic benefits, for both coastal communities and the mainland agricultural sector. Objective: to evaluate the osmoregulatory capacity of juvenile goliath grouper when exposed to low-salinity water. Methods: juvenile goliath grouper (Epinephelus itajara) were either directly or gradually transferred from seawater to freshwater to test osmoregulatory ability. Body weight was assessed during acclimation and blood samples were taken to measure total osmolality and electrolytes. Results: all fish survived the transfer to freshwater and were maintained for up to 12 days after termination of the acclimation trials which lasted 72 hours. Juvenile goliath grouper were hyposmotic (342-462 mosmol/kg) to seawater and hyperosmotic (272-292 mosmol/kg) to freshwater. The gills and kidneys were found to have principal roles in the osmoregulatory processes. Numerous chloride cells were found on superficial regions of the gill filament epithelium, most likely serving to eliminate the excess of electrolytes while in seawater. The kidneys had numerous nephrons to make urine and retain electrolytes while in freshwater. Conclusions: these observations lead to the conclusions that juvenile goliath grouper have the ability to osmoregulate in freshwater and should be considered a marine euryhaline species. Such adaptability opens for consideration the possibility that goliath grouper could be successfully farmed in brackish water or even in freshwater.